Educational Activities of Omsk Medical Society in Late XIX - Early XX Century - K. S. Barabanova (Научный диалог)
At the end of XIX - beginning of XX centuries members of the Omsk Medical Society began to give public lectures to the townspeople. During this period, doctors throughout the Russian Empire carried out active educational activities, the purpose of which was to familiarize society with new sanitary practices and prevent epidemics. The purpose of this article is to study the educational activities of Omsk doctors in the late 19th - early 20th centuries, to achieve which we will turn to the issues that the lecturers raised in their speeches and their professional qualifications. For their presentations, lecturers chose topics related to both general issues of the development of medical science and addressed local sanitary problems. So public lectures became a platform for discussing urban problems. Doctors acted as experts, both for the authorities and for the townspeople. Omsk doctors were welltrained specialists with extensive practical experience, as well as actively engaged in scientific activities. Reading public lectures gave them the opportunity to take part in the educational activities of the scientific societies of Omsk, as well as to do charity work.